ASSISTANCE WITH SIMPLE FINANCIAL ACCOUNTING MANAGEMENT FOR MSMEs TO SUPPORT SUSTAINABLE FINANCIAL DEVELOPMENT - Zunaidi, Arif; Nur Fadhilah, Amalia; Lailatul Maghfiroh, Fachrial (Proceedings of Annual Conference on Community Engagement, 2024)
This service activity aims to increase the financial capacity of micro, small, and medium enterprises (MSMEs) through simple accounting training, with a focus on effective financial recording. The participants, consisting of experienced MSME players and novice students, initially faced difficulties in recording their business transactions. However, through practice and discussion, they managed to overcome these obstacles and were able to record their finances more simply. This program reflects the importance of simple accounting in supporting inclusive and sustainable economic growth, in accordance with the Sustainable Development Goals (SDG). The participants were satisfied with the results of this training and even suggested the establishment of an ongoing consultation forum. This practical approach has helped them understand the importance of accounting, contributed to improving financial skills, and opened up opportunities for a more sustainable economy.